2005
DOI: 10.1097/01.psy.0000160461.19239.13
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Awareness Deficits in Inpatients of a Psychosomatic Ward: A Comparison of Two Different Measures of Alexithymia

Abstract: The LEAS captured a change in emotional awareness due to treatment, whereas the TAS 20 captured a change in negative affect. The LEAS appears to be a more specific measure of change in emotional awareness in clinical contexts than the TAS 20.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
126
1
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 161 publications
(142 citation statements)
references
References 39 publications
11
126
1
4
Order By: Relevance
“…In relative accordance with literature (Lumley 2000), in our study EOT did not correlate with depression (although it was related with anxiety), and the same was observed with LEAS scores. Subic-Wrana et al (2005) suggested that perhaps the measurement of the words used to express affect, provided by the LEAS scoring system, captures better the deficits in symbolizing capacities at a level that is not substantially interfered by negative affect, than does TAS-20. These considerations support the relevance for considering both measures in assessing emotional regulation deficits: one of them seems to be more sensitive to the presence of negative affect and to emotional developmental dimensions, and the other one more specific in measuring the representational abilities or deficits in a way that seems to be less interfered by the quality of affect.…”
Section: Discussionmentioning
confidence: 99%
“…In relative accordance with literature (Lumley 2000), in our study EOT did not correlate with depression (although it was related with anxiety), and the same was observed with LEAS scores. Subic-Wrana et al (2005) suggested that perhaps the measurement of the words used to express affect, provided by the LEAS scoring system, captures better the deficits in symbolizing capacities at a level that is not substantially interfered by negative affect, than does TAS-20. These considerations support the relevance for considering both measures in assessing emotional regulation deficits: one of them seems to be more sensitive to the presence of negative affect and to emotional developmental dimensions, and the other one more specific in measuring the representational abilities or deficits in a way that seems to be less interfered by the quality of affect.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 For patients experiencing panic seemingly out of the blue, we considered the LEAS a potentially important patient variable. Indeed, baseline LEAS had a strong effect at treatment termination.…”
Section: Limitationsmentioning
confidence: 99%
“…Research has shown alexithymia to be a relatively stable trait under changing emotion, stress, and pathology levels (Luminet, Bagby, & Taylor, 2001; Mikolajczak & Luminet, 2006;Subic-Wrana, Bruder, Thomas, Lane, & Kohle, 2005).…”
Section: Introductionmentioning
confidence: 99%